Defend-protect-support : the evolution of the Irish Military 1956-1978 - Campbell, Niamh (Trinity College (Dublin, Ireland). Department of History, 2014)
This thesis is a study of the evolution of Irish Defence Forces from the period 1956 until 1978. The Coxian approach was used to provide a conceptual framework. Coxian historicism questions how the prevailing system developed by revealing the historical structures characteristic of particular eras. It is grounded in both critical theory and historicism, and acknowledges the importance of structures and institutions while placing heavy emphasis on empirical analysis.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin